GENETIC DIVERGENCE IN MAIZE (Zea mays L.) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
Genetic divergence of 25 genotypes of maize were estimated using D2 and Principal Component Analysis. The genotypes under study fell into five clusters. The inter-cluster distances were higher than intra cluster distances suggesting wider genetic diversity among the genotypes of different groups. The intra-cluster value was maximum in cluster V and minimum in cluster I. The inter cluster D2 values showed the maximum distance between cluster II and III followed by the distance between II and I. The cluster means were higher for days to maturity, plant height and ear height in cluster II; grain yield per plant was higher in cluster IV. Genotypes were much in use having the above mentioned characters in clusters II and IV would offer a good scope for the improvement of this crop through hybridization and rational selection.DOI: http://dx.doi.org/10.3329/bjpbg.v20i1.17027